Measuring the Implementation of Codes of Conduct. An Assessment Method Based on a Process Approach of the Responsible Organisation - Nijhof, André (Journal of business ethics, 2003)
More and more organisations formulate a code of conduct in order to stimulate responsible behaviour among their members. Much time and energy is usually spent fixing the content of the code but many organisations get stuck in the challenge of implementing and maintaining the code. The code then turns into nothing else than the notorious "paper in the drawer", without achieving its aims. The challenge of implementation is to utilize the dynamics which have emerged from the formulation of the code. This will support a continuous process of reflection on the central values and standards contained in the code. This paper presents an assessment method, based on the EFQM model, which intends to support this implementation process.